1994
DOI: 10.1007/bf01257120
|View full text |Cite
|
Sign up to set email alerts
|

Uptake from water, depuration and tissue distribution of110mAg in a freshwater fish,Cyprinus carpio L.

Abstract: Abstract. Radionuclide accumulation was studied on a group of 20 fish maintained at 20 • 1 ~ in spring water containing 30 Bq mL -1 of 110mAg. Because of a very significant radionuclide adsorption onto available surfaces and in order to simulate chronic exposure, the water was completely renewed three times a week. Accumulation of 110mAg was slow, with an estimated time to maximum contamination level of 180 days. The concentration factor, calculated from the ratio of the integrals of the curves representing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Due to the corresponding biological half-lives of 0.8 and 30 days, respectively, the fish retained about 30% of the initial l l~ within 6 weeks [7].…”
Section: Excretion Of L L~mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the corresponding biological half-lives of 0.8 and 30 days, respectively, the fish retained about 30% of the initial l l~ within 6 weeks [7].…”
Section: Excretion Of L L~mentioning
confidence: 99%
“…Baudin et al [7] reported that accumulation of l l0mAg in a freshwater fish, Cyprinus-carpio L, was slow with an estimated time to maximum contamination level of 180 days. They noted that although the liver and digestive tract only represented about 4 and 10% of the total body mass, respectively, these two organs accounted for 30-40% of the total radionuclide body burden.…”
Section: Introductionmentioning
confidence: 99%
“…Because BCFs, ␣, and k e in carp and trout show substantial differences (Table 1), carp and trout were modeled separately. Mean steady-state BCFs extrapolated from laboratory data served as point estimates for brown trout (Salmo trutta) [35] and common carp (Cyprinus carpio) [36]. To estimate variation, confidence intervals for weekly mean Ag concentrations in trout over the uptake period were converted to geometric standard Aquatic silver bioaccumulation and human health risks Environ.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…Ingestion of Ag through contaminated fish and treated drinking water was estimated for freshwater anglers and subsistence fishers ( Table 2). For this protective, screening-level assessment, 90th percentile Ag concentrations in whole fish were converted to wet-weight muscle concentrations C f (mg/ kg) assuming a moisture content of 0.74 for both fish species and muscle:whole-fish concentration ratios of 0.11 and 0.25 for trout and carp, respectively [35,36,39,40]. The Ag dose from fish consumption I f (mg/kg/d) is [47] C · IR · ␣ · EF· ED…”
Section: Human Ag Exposurementioning
confidence: 99%